Innovations of AI-Generated Content (AIGC) in Stage Art: Exploring from Theory to Practice - Wu, Siyu; Huang, Siyang (Transactions on Economics, Business and Management Research, 2024)
The integration of Artificial Intelligence-Generated Content (AIGC) within stage art heralds a new era of creative possibilities, merging traditional performance techniques with cutting-edge technology. This paper explores the implications, challenges, and prospects of incorporating AIGC into stage productions, drawing on insights from industry professionals and audience feedback. Through mixed-method research involving interviews and surveys, we uncover the diverse ways in which AIGC is reshaping creative processes, enhancing audience engagement, and redefining the boundaries of stage art. Our findings reveal a complex landscape where technological innovation coexists with concerns about authenticity and artistic integrity. By delving into the nuances of this integration, we aim to provide a balanced perspective on the potential of AIGC to enrich stage art while maintaining its human essence. This study contributes to the ongoing discourse on the role of technology in the arts and offers a foundation for future research and practical applications in the field.